1999
DOI: 10.1038/23611
|View full text |Cite
|
Sign up to set email alerts
|

Prelude or requiem for the ‘Mozart effect’?

Abstract: Rauscher et al. reported [1] that brief exposure to a Mozart piano sonata produces a temporary increase in spatial reasoning scores, amounting to the equivalent of 8-9 IQ points on the Stanford-Binet IQ scale [2]. Early attempts to confirm this 'Mozart effect' were unsuccessful [3, 4, 5, 6]. Rauscher et al. subsequently restricted their account to an improvement in spatialtemporal reasoning, as measured by the Paper Folding and Cutting task [7]. We use procedures modelled on the original report to show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
43
0
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 1 publication
2
43
0
8
Order By: Relevance
“…Nantais & Schellenberg, 1999), despite failures to replicate the finding (cf. Č rnîcec, Wilson, & Prior, 2006;Steele et al, 1999;McKelvie & Low, 2002), and despite careful assurances from the original authors that their study did not prove a broad relationship between musical exposure and intelligence (Rauscher, 1999), the popular conclusion-that classical music, and especially Mozart, is uniquely endowed with brainboosting powers-proved difficult to dislodge. In 1998, the governor of Georgia initiated a bill to provide classical music CDs free to new mothers (Sack, 1998), and the state of Florida passed a bill requiring all state-funded day-care centers to play classical music every day (State of Florida, 1998).…”
mentioning
confidence: 99%
“…Nantais & Schellenberg, 1999), despite failures to replicate the finding (cf. Č rnîcec, Wilson, & Prior, 2006;Steele et al, 1999;McKelvie & Low, 2002), and despite careful assurances from the original authors that their study did not prove a broad relationship between musical exposure and intelligence (Rauscher, 1999), the popular conclusion-that classical music, and especially Mozart, is uniquely endowed with brainboosting powers-proved difficult to dislodge. In 1998, the governor of Georgia initiated a bill to provide classical music CDs free to new mothers (Sack, 1998), and the state of Florida passed a bill requiring all state-funded day-care centers to play classical music every day (State of Florida, 1998).…”
mentioning
confidence: 99%
“…Controversy has emerged over the existence of the effect (3,8,16,18). In a series of studies, Rideout and colleagues (12,13,14) obtained results consistent with an effect.…”
mentioning
confidence: 75%
“…Both Chabris (3) and Nantais and Schellenberg (6) have proposed, using similar reasoning, that arousal and differences in listening-preference may explain results related to the Mozart effect. Steele and colleagues (16,18) included silence as a neutral condition, measured subjects' mood, and obtained results that indicated both the Mozart and relaxation conditions produced significant arousal changes in the directions suggested by the literature. In contrast, Rideout's studies (12,13,14) have not employed a neural arousal condition nor measured mood.…”
mentioning
confidence: 99%
“…More laboratories have been unable to produce a Mozart effect (Bridgett & Cuevas, 2000;Carstens, Huskins, & Hounshell, 1995;Kenealy & Monsef, 1994;McCutcheon, 2000;McKelvie & Low, 2002;Newman, Rosenbach, Burns, Latimer, Matocha, & Vogt, 1995;Ong, Lu, & Smith, 2000;Steele, Bass, & Crook, 1999;Steele, Dalla Bella, et al, 1999;Stephenson, 2002;Stough, Kerkin, Bates, & Mangan, 1994;Weeks, 1996) than have been able to produce the effect (Nantais & Schellenberg, 1999;Rideout & Laubach, 1996). Even positive results have been interpreted as being explained by arousal or preference differences instead of musical priming of spatial reasoning areas of the brain (Chabris, 1999;Husain, Thompson, & Schellenberg, 2002;Nantais & Schellenberg, 1999;Steele, 2000;Steele, Ball, & Runk, 1997;Thompson, Schellenberg, & Husain, 2001).…”
mentioning
confidence: 99%
“…However Steele, Bass, and Crook (1999) replicated the procedure of Rauscher et al (1995) and were unable to produce a Mozart effect. Steele, Dalla Bella, Peretz, et al (1999) were unable to produce a Mozart effect in three experiments that used the general procedures of both experiments by Rauscher et al Rauscher (1999b) suggested these negative results were caused by procedural artifacts. Rauscher's main criticism was Steele et al's use of random assignment of subjects to experimental conditions.…”
mentioning
confidence: 99%